SCIENTIFIC PRINCIPLES OF OPTICAL METHOD FOR DETERMINING THE SEMICYCLIC AND SINGLE-CYCLIC DEFORMATION OF TEXTILE YARNS (Western European Journal of Modern Experiments and Scientific Methods, 2025)
The article elucidates the scientific foundations for determining the half- and full-cycle deformation of textile yarns using optical methods. The study analyzed the advantages of optical measurements over traditional mechanical techniques in terms of accuracy and noncontact operation. Using a device developed based on Digital Image Correlation (DIC) technology, the tensile, relaxation, and elastic properties of yarns were investigated. Experimental results demonstrated that the optical method allows high-precision, real-time monitoring of the deformation process. This approach holds significant importance for evaluating the quality of textile products and optimizing production processes